Canine idiopathic chronic hepatitis - Bexfield, Nicholas (Elsevier, 2017)
Canine idiopathic hepatitis is a common disease, categorized histologically by presence of hepatocellular apoptosis or necrosis, a variable mononuclear or mixed inflammatory cell infiltrate, regeneration and fibrosis.